(3RHOI GdHjGf aj HQGgjf CMcGe GdbQBf hJaSjQ BjGJ CMcGe GdbQBfs - (3GdCQOHjdj, CMeO Hf eMeO GdCQOHjdj, J (B993(3g` (B1585(3es ((3eMeO GdbgHGFjs)
(3ChdgG (B:s
(3ChdgG(B: (3GYde Cf ggfG aGFOI dGHO bHd GdTQhY aj GdebUhO GdETGQI EdjgG, hgj Cf GdeTghQ Hjf GdWdHI Cfg dG jLhR JaSjQ GdbQBfs
(3BNQgG (B:s
(3BNQgG(B: (3hCfJ YQaJ Cfg djS HLjO heKd gPG aYd aj cKjQ ef GdBjGJ MjK oYeeJ eY chf SHH GdfRhd NGUG deG eQ Ke Ydi JbOjQ GdJNUU CjkVG dG jHYO GdJYeje dage GdYdI ajSJNQL GdHGbj aJCed(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B1: 234s
(3GdPQjYI, L (B12: 17s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs